Structure-property relationships of photofunctional diiridium(II) complexes with tetracationic charge and an unsupported Ir–Ir bond - Fangrui Zheng; Yuhong Yang; Siye Wu; Shunan Zhao; Yifan Zhu; Huimin Su; Jun-Feng Dai; Zeyin Yan; Lung Wa Chung; Keith Man-Chung Wong (Communications Chemistry)
Abstract In contrast to the extensively studied dirhodium(II) complexes and iridium(III) complexes, neutral or dicationic dinuclear iridium(II) complexes with an unsupported ligand are underdeveloped. Here, a series of tetracationic dinuclear iridium(II) complexes, featuring the unsupported Ir(II)–Ir(II) single bond with long bond distances (2.8942(4)–2.9731(4) Å), are synthesized and structurally characterized. Interestingly, compared to the previous unsupported neutral or dicationic diiridium(II) complexes, our DFT and high-level DLPNO-CCSD(T) results found the largest binding energy in these tetracationic complexes even with the long Ir(II)–Ir(II) bond. Our study further reveals that London dispersion interactions enhance the stability cooperatively and significantly to overcome the strong electrostatic repulsion between two half dicationic metal fragments. This class of complexes also exhibit photoluminescence in solution and solid states, which, to our knowledge, represents the first example of this unsupported dinuclear iridium(II) system. In addition, their photoreactivity involving the generation of iridium(II) radical monomer from homolytic cleavage was also explored. The experimental results of photophysical and photochemical behaviours were also correlated with computational studies.